A study of development mode of collapse with variation of strains and stresses during compression of metallic shells having dome-cone shape. (May 2018) - Gupta, P.K.; Gupta, N.K.
Abstract: The present paper deals with the experimental and computational analysis of the deformation behaviour of the metallic thin walled aluminium shells having dome-cone combined geometry. The specimens were tested on a universal testing machine INSTRON under axial compression to identify their modes of collapse and to study the associated energy absorption capacity. In experiments all the shell specimens were found to collapse with the formation of an axisymmetric mode of collapse due to development of the associated plastic Zones in dome and cones. A Finite Element computational model of development of the axisymmetric mode of collapse is presented and analysed, using a non-linear finite element code FORGE2. The proposed finite element model for this purpose idealizes the deformation as axisymmetric. Six noded triangular elements were used to discretize the domain. The material of the shell specimens was idealized as rigid visco-plastic. Experimental and computed results of the deformed shapes and their corresponding load-compression and energy-compression curves were presented and compared to validate the computational model. Typical variations of equivalent strain, equivalent strain rate and nodal velocity distribution are presented to help in predicting the mode of collapse. On the basis of the obtained results development of the axisymmetric mode of collapse has been presented, analysed and discussed. Highlights: Analysis of deformation behaviour of the thin walled aluminium shells having dome-cone combined geometry is presented. Modes of collapse with the development of the plastic zones is studied with the associated energy absorption capacity. A FE model of development of the axisymmetric mode of collapse is presented and analysed, using code FORGE2. Typical variations of equivalent strain rate, strain and nodal velocity are presented to help in predicting the mode of collapse. Development of the axisymmetric mode of collapse has been presented, analysed and discussed.